The problem of the Lengyel Culture in Northern Croatia - Težak-Gregl, Tihomila (Array, 2000)
The paper discusses the problem of the Lengyel Culture in norther Croatia. It was introduced into the Croatian Prehistory by R. R. Schmidt for some pottery finds from Bapska. The term was leter accepted by V. Milojčić and S. Dimitrijević to describe the present-day Sopot Culture. The Lengyel features were also detected in the Brezovljani type of the Sopot Culture. But recently a new regonal variant of late Lengyel Culture was determinated at the site of Ozalj. in northwestern part of Croatia which is very close to the late Neolithic finds in continental Slovenia and western Transdanubia.